The Local Release of Teriparatide Incorporated in 45S5 Bioglass Promotes a Beneficial Effect on Osteogenic Cells and Bone Repair in Calvarial Defects in Ovariectomized Rats - de Araújo, Juliani Caroline Ribeiro [UNESP]; Sobral Silva, Leonardo Alvares [UNESP]; de Barros Lima, Vinicius Almeida [UNESP]; Bastos Campos, Tiago Moreira; Lisboa Filho, Paulo Noronha [UNESP]; Okamoto, Roberta [UNESP]; de Vasconcellos, Luana Marotta Reis [UNESP] (MDPI, 2023)
With the increase in the population’s life expectancy, there has also been an increase in the rate of osteoporosis, which has expanded the search for strategies to regenerate bone tissue. The ultrasonic sonochemical technique was chosen for the functionalization of the 45S5 bioglass. The samples after the sonochemical process were divided into (a) functionalized bioglass (BG) and (b) functionalized bioglass with 10% teriparatide (BGT). Isolated mesenchymal cells (hMSC) from femurs of ovariectomized rats were differentiated into osteoblasts and submitted to in vitro tests. Bilateral ovariectomy (OVX) and sham ovariectomy (Sham) surgeries were performed in fifty-five female Wistar rats. After a period of 60 days, critical bone defects of 5.0 mm were created in the calvaria of these animals. For biomechanical evaluation, critical bone defects of 3.0 mm were performed in the tibias of some of these rats. The groups were divided into the clot (control) group, the BG group, and the BGT group. After the sonochemical process, the samples showed modified chemical topographic and morphological characteristics, indicating that the surface was chemically altered by the functionalization of the particles. The cell environment was conducive to cell adhesion and differentiation, and the BG and BGT groups did not show cytotoxicity. In addition, the experimental groups exhibited characteristics of new bone formation with the presence of bone tissue in both periods, with the BGT group and the OVX group statistically differing from the other groups (p < 0.05) in both periods. Local treatment with the drug teriparatide in ovariectomized animals promoted positive effects on bone tissue, and longitudinal studies should be carried out to provide additional information on the biological performance of the mutual action between the bioglass and the release of the drug teriparatide.
Keywords: biocompatible materials; bone regeneration; cell differentiation; osteoporosis; teriparatide